Giant-Cell Arteritis - Chaudhry, Imtiaz A. (IntechOpen, 2022)
Giant cell arteritis (GCA) is a systemic vasculitis that affects medium- to large-size arteries in which an inflammatory reaction destroys the media of the artery wall with the fragmentation of the elastic lamina, which can result in acute vision loss if not treated in a timely manner. The other common visual symptoms may include diplopia due to cranial nerve palsies and transient visual loss. This book provides a comprehensive overview of GCA, with chapters on epidemiology, cellular and molecular characteristics of the disease, extra-cranial involvement of GCA, medical imaging, and much more.